Comparative study of school principals' leadership practices: Lessons for Chile from a cross-country analysis. (March 2018) - Marfan, Javiera; Pascual, Javier
The article reports the results of a cross-country educational research project that uses quantitative methods to identify school leadership practices and contextual characteristics that contribute to explain student achievement in Chile, considering international comparisons. The results question previous evidence about a common repertoire of effective leadership practices and suggest that local context will affect the type of leadership that is required for a specific educational system to improve, and therefore the definition of principals' effective practices. For Chile, the article points out that the principals' leadership practices that contribute the most to improve teacher performance are those related to ensuring that teachers' work and professional development are in accordance with the teaching goals of the school, as well as monitoring student work and classroom activities. Nevertheless, Chilean principals are more likely to get involved in the former practices (related to the school teaching goals) than in those related to teachers' work in the classroom, resulting in their actions being more powerful in mobilizing teachers' attitudes and professional practices than their teaching, which reduces their potential to promote teachers' performance. The results have implications for educational leadership research and policy making, especially in non-Anglo-American countries.